2014
DOI: 10.2147/ijn.s69845
|View full text |Cite
|
Sign up to set email alerts
|

Microbubbles coupled to methotrexate-loaded liposomes for ultrasound-mediated delivery of methotrexate across the blood–brain barrier

Abstract: Methotrexate (MTX) is the single most effective agent for the treatment of primary central nervous system lymphoma. Currently, the delivery of MTX to the brain is achieved by high systemic doses, which cause severe long-term neurotoxicity, or intrathecal administration, which is highly invasive and may lead to infections or hemorrhagic complications. Acoustically active microbubbles have been developed as drug carriers for the noninvasive and brain-targeted delivery of therapeutics. However, their application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Many researchers have focused on establishing the sonoporation system as an effective non-viral drug delivery method. Sonoporation strategies have also been developed with various types of MBs for targeted delivery [ 25 , 26 ]. Liao et al demonstrated that the combination of EGFR-targeting MBs and US exposure effectively eliminates tumor cells in vivo [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have focused on establishing the sonoporation system as an effective non-viral drug delivery method. Sonoporation strategies have also been developed with various types of MBs for targeted delivery [ 25 , 26 ]. Liao et al demonstrated that the combination of EGFR-targeting MBs and US exposure effectively eliminates tumor cells in vivo [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animals were anesthetized and placed supine on a positioning sled for MRI. Brain ultrasound treatment was conducted under the following settings: 1 MHz, 20% duty cycle, and an ultrasound intensity of 2 W/cm 2 (Wang et al, 2014 ). After injecting PLs-MBs (0.01 ml/kg body weight) and PLs-GDNF-MBs (0.01 ml/kg body weight) into the tail vein for 30 min, FUS was performed.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, coupling gene-loaded liposomes to the microbubble surface is adopted (Lentacker et al, 2010 ). This approach takes full advantage of the high DNA-carrying capacity of PLs and the ultrasound-mediated BBB disruption effect of MBs (Wang et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thirty Wistar rats (200 ± 20 g; Huafukang Biotechnology Company, Beijing, China) were fed pellet feed for a week in cages before the experiment. The rats were divided equally into three groups: (a) non-mCEUS control group; (b) continuous launch of mCEUS [ 18 ]; and (c) intermittent mCEUS launches (400-ms interval) [ 18 ]. Before undergoing mCEUS, the rats were anesthetized by intraperitoneal injection of pentobarbital sodium (3%, 30 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…Microbubble contrast suspension containing 8 μ l (45 μ g) of sulfur hexafluoride per ml (Third Military Medical University) was injected (1 ml/kg, both mCEUS groups) via the tail vein [ 18 ]. Continuous or intermittent mCUES was applied to each rat for a period of 10 min via a Philips IE33 (USA) ultrasonic diagnostic machine with an S5-1 probe (harmonic frequency, 1.7/3.3 MHz; mechanical index, 0.8 mI; and treatment time, 10 min) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%